DIALEKTIKA IDEALISME DAN REALISME DALAM KEPEMIMPINAN VISIONER ABAD 21 DI SEKOLAH MENENGAH ISLAM : PERSPEKTIF MANAJEMEN PENDIDIKAN - Kurniawati, Evi; Rachmawati, Siti Dewi; Nandang, Nandang (Jurnal Manajemen Pendidikan, 2026)
This study examines how the philosophies of idealism and realism are articulated and integrated into the practice of 21st-century visionary leadership at the secondary education level, using SMAIT Mentari Ilmu Karawang as a case study. The study adopts an interpretive qualitative approach with a phenomenological orientation to explore how educational leaders and teachers experience, interpret, and negotiate ideal values and managerial realities in everyday leadership practice. Data were collected through in-depth interviews, focus group discussions, and institutional document analysis, and analyzed thematically through a triangulated process. The findings indicate that leadership idealism is strongly reflected in the educational vision and the internalization of transcendental values, while leadership realism is manifested through managerial systems, performance evaluations, and decision-making processes. Integration between idealism and realism is not primarily embedded in formal policies but emerges through relational leadership practices, particularly through teachers' roles as agents of vision implementation. This study proposes a dialectical idealism–realism model that conceptualizes visionary leadership as a reflective and adaptive process, highlighting the managerial importance of balancing structural effectiveness with relational leadership to sustain the educational vision.